Stress and Coping in Parents of Children and Adolescents with Spinal Muscular Atrophy - von Gontard, A.; Rudnik-Schöneborn, S.; Zerres, K. (Klinische Pädiatrie, 2012)
Chronic illness and disability is not only associated with higher rates of behavioural problems in children, but also parental stress which requires active coping. The aim of the study was to analyse stress and coping, as well as their mediating variables, in parents of children and adolescents with Spinal Muscular Atrophy (SMA).96 children and adolescents with SMA aged 6;0 to 18;11 years were compared to 59 age, sex and SES matched controls. Parental stress was measured with the QRS, coping with the F-COPES and social support with the F-SOZU questionnaires.Parental stress was significantly higher in the SMA families for the total score and all subscales of the QRS. Stress was higher in families with severely affected SMA types I and II. The greatest percentage of variance contributing to stress could be explained by lack of social support, degree of disability and behavioural problems in the child. Although social support was reduced, the actual coping abilities of the families did not differ.Families with children and adolescents with SMA show high degrees of stress and strain which are associated with the severity of the disease, reduced social support and child behaviour. Despite these stresses they manage and cope no differently from families with healthy children.
Keywords: parental stress; parental coping; QRS questionnaire; F-COPES questionnaire; chronic ill children; chronic disabled children